It is necessary to limit the term of office of the House of Representatives to prevent abuse of authority in Indonesia - Vicki Dwi Purnomo; Suryawan Raharjo; Aida Dewi (Formosa Journal of Applied Sciences, 2023)
In Indonesia, the limitation of power has been implemented in the constitution which regulates the term of office of the President and Vice President. The limitation of the President's term of office is an attempt to prevent the incumbent from continuing in power which is the reason for absolute power. There are no regulations that apply to DPR members. There is no provision which states that a candidate for members of the Legislative Body who has served as a member of the Legislative Body for 2 (two) terms cannot return to serve as President. The large number of board members who are caught in corruption cases has created a negative public perception. Indonesia adheres to the principle of democracy or people's sovereignty which guarantees citizen participation in the decision-making process within the state, so that many laws and regulations that are implemented and enforced represent the realization of justice and legal certainty.